Review on a Oral Mucoadhesive Drug Delivery System - Mahadik, R.A.; Redasani, V. K.; Jadhav, P.D.; Bhagat, P.D. (Asian Journal of Pharmaceutical Research and Development, 2023)
Since the previous four decades, the idea of mucoadhesion has attracted significant interest across a range of pharmaceutics domains.Because mucosal membranes are relatively permeable, the mucoadhesive drug delivery system is a well-liked innovative drug delivery technique, allowing for the rapid uptake of a medication into the systemic circulation and avoiding the first pass metabolism. Recent years have seen the development of a number of mucoadhesive drug delivery systems for nasal, buccal, oral, vaginal, and rectal routes for both local and systemic effects.The mucus membrane, which covers the mucin molecules and the mucosal epithelial surface, can interact with mucoadhesive drug delivery systems. This interaction increases the dosage form’s residence time at the site of absorption, increasing medication bioavailability and effectiveness while also enhancing therapeutic results.